PEOPLE WITH SPECIAL NEEDS AND THEIR EMPLOYMENT PROBABILITY: A MALAYSIAN PERSPECTIVE - Maideen, Mazuwin Binti Haja; Munusamy, Prof. Dr Jayaraman (IJRDO - Journal of Business Management, 2017)
This literature attempts to identify the driving factors and interceptions of occupation for individuals with inability in Malaysian region. It deeply investigates the abilities and mental attributes required by individuals with special needs keeping in mind the end goal to contribute in occupational scenario and the obstacles associated with this. Secured source of income has a specific level of constructive effect on individuals with incapacities considering fiscal dependability and mental stability. Occupational capacity not just gives a wellspring of wages to liberated breathing but additionally builds one's intelligence of acknowledgment and sense of pride. Actually higher portion of individuals with inability are teachable and can be considered for recruitment related to various occupations. If provided suitable occupational options, this segment can hugely subsidise nation’s progress also inclusive of Tax paying opportunity. Accordingly, it is assessed that individuals with inabilities could enrich about USD 1.68 billion to the Malaysian GDP. Subsequently, they ought not be seen and regarded as an obligation or burden to community.